Nontuberculous mycobacteria by metagenomic next-generation sequencing: Three cases reports and literature review - Ying Liu; Xiaoxu Ma; Jiajun Chen; Huifen Wang; Zujiang Yu (Frontiers in Public Health, 2022)
BackgroundThe increasing worldwide incidence of nontuberculous mycobacterial lung disease (NTM-LD) and the similarity of its manifestations to those of tuberculosis (TB) pose huge challenges in the diagnosis and treatment of NTM-LD, which is commonly misdiagnosed and mistreated as TB. Proper diagnosis and treatment at an early stage can greatly improve patient outcomes.Case presentationMycobacterium avium was identified by mNGS in lung tissue of case 1 and bronchioalveolar fluid from case 2 that was not identified using conventional microbiological methods. Multiple NTM species were detected in the blood mNGS samples from case 3 who had disseminated NTM infection. Although NTM was isolated from blood culture, conventional methods failed to identify the organisms to the level of species. All three patients were suffering from and being treated for myelodysplastic syndrome, rheumatoid arthritis, systemic lupus erythematosus, or acute lymphoblastic leukemia, making them immunosuppressed and susceptible to NTM infections. Case 1 and Case 2 significantly improved after anti-NTM treatment, but case 3 succumbed to the infection due to her underlying medical illness despite aggressive treatment.ConclusionsThe cases in this study demonstrate the effectiveness of mNGS in facilitating and improving the clinical diagnosis of NTM infections. We propose combining mNGS with traditional diagnostic methods to identify pathogens at the early stages of the disease so that targeted treatment can be implemented.